Două perspective în explicarea satisfacţiei față de viaţă: top-down vs. bottom-up - Mihalache, Florentin Flavius (Calitatea Vieții, 2008)
Life satisfaction represents a product or a factor of life domains satisfaction? To this question, we want to offer an answer in this study. Analysing the models top-down and bottom-up we want to discover which of these perspectives is better upholded by some empirical data. In this analysis we have used two major data sources: the research BOP from May 2006 and some panel data from ICCV Quality of Life Diagnosis (for the years 1997 and 1998). The analysis of these data wants to obtain an image of subjective well-being construct in Romanian society.